Food availability is crucial for effects of 1-μm polystyrene beads on the nematode Caenorhabditis elegans in freshwater sediments. (July 2022) - Höss, Sebastian; Rauchschwalbe, Marie-Theres; Fueser, Hendrik; Traunspurger, Walter
Abstract: Freshwater sediments represent a sink for microplastic (<5 mm) through various processes. Thus, benthic organisms can be exposed to relatively high concentrations of microplastics. Surprisingly, studies on benthic organisms are still underrepresented in the field of ecotoxicological effect assessment of microplastics. Therefore, we studied the effects of 1-μm polystyrene (PS) beads on the reproduction of the nematode Caenorhabditis elegans using a standardized protocol for toxicity testing in freshwater sediments (96 h; ISO 10872:2020), combined with ingestion experiments using fluorescent PS beads. To investigate the role of sediment properties (e.g., textures, organic contents) for ingestion and effects of PS beads, five different artificial and field-collected sediments were used. Body burdens of 1-μm PS beads in the intestinal tract of the nematodes after 96 h differed between the sediments, however, differences were not significant over the whole course of the experiment. EC10 and EC50-values of 1-μm PS beads for C. elegans ' reproduction in the various sediments ranged from 0.9 to 2.0 and 4.8 to 11.3 mg PS/g dry sediment, respectively. The ECx-values showed to be considerably higher than values reported for water exposure (EC10/50: 0.2 and 0.6 mg PS/ml, respectively), which was probably due to higher food densities in sediment compared to water exposure. Based on the PS beads/bacteria ratio, ECx-values were comparable between sediment and water exposure, suggesting that also in sediments microplastic reduces the food availability for C. elegans causing lower reproduction. This indirect effect mechanism was confirmed by experiments with varying food densities. Thus, the nutritious conditions might play a crucial role for the overall ecological risk of microplastics in benthic ecosystems. Graphical abstract: Image 1 Highlights: First study of the interaction between freshwater sediment, PS beads and nematodes. Neither PS bead ingestion, nor their effect on C. elegans were related to sediment type. Ratio of PS beads to food bacteria explains toxic effects matrix-independently. Food availability is a crucial mechanism for negative effects on reproduction.